2016
DOI: 10.3109/15376516.2016.1158340
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect ofDunaliellasp., lipid extract rich in polyunsaturated fatty acids, on hepatic and renal toxicity induced by nickel in rats

Abstract: LE of Dunaliella sp., rich in PUFA has been proven to be effective in protection against Ni-induced toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…Through the absence of enough GPx activity or GSH levels, LOP and hydrogen peroxide are not detoxified and perhaps converted by transition metals to hydroxyl radicals and lipid peroxyl radicals. The findings were similar to the results of Kubrak et al [36] and Dahmen-Ben Moussa et al [21] who found decreased GPx, CAT and SOD activities in the rat kidney by Ni cytotoxicty of antioxidant capacity may be coupled with the depletion of GSH and reduced total sulfhydryl contents or with their increased utilization for quenching free radicals and/or their inactivation by excessive Ni oxidation. Furthermore, Ni was reported to trigger nitric oxide (NO) creation [43], which may inhibit both CAT activities by binding to its heme prosthetic group [44] and GPx activity [45].…”
Section: Bouhalit and Kechridsupporting
confidence: 81%
See 1 more Smart Citation
“…Through the absence of enough GPx activity or GSH levels, LOP and hydrogen peroxide are not detoxified and perhaps converted by transition metals to hydroxyl radicals and lipid peroxyl radicals. The findings were similar to the results of Kubrak et al [36] and Dahmen-Ben Moussa et al [21] who found decreased GPx, CAT and SOD activities in the rat kidney by Ni cytotoxicty of antioxidant capacity may be coupled with the depletion of GSH and reduced total sulfhydryl contents or with their increased utilization for quenching free radicals and/or their inactivation by excessive Ni oxidation. Furthermore, Ni was reported to trigger nitric oxide (NO) creation [43], which may inhibit both CAT activities by binding to its heme prosthetic group [44] and GPx activity [45].…”
Section: Bouhalit and Kechridsupporting
confidence: 81%
“…Our results were in accordance with those reported by Amudha and Pari [2], who mentioned a significant increase in the relative kidney weight in Nitreated male rats. However, our results were opposing those reported by Dahmen-Ben Moussa et al [21] and Adeyemi and Elebiy [20] who exhibited that Ni treatment resulted in a significant decrease in relative kidney weight. In the present work, coadministration of methionine prevented changes in relative kidney weight and body weights.…”
Section: Bouhalit and Kechridcontrasting
confidence: 57%
“…Nickel is a silvery-white transition metal that takes on a high polish. The toxicity of nickel depends on the way of its exposure and the solubility of the compound like other metals [41].…”
Section: Removal Of Metal Ions With Imprinted Materialsmentioning
confidence: 99%
“…Dunaliella sp. CTM 20028 have been isolated for the first time from Chott El-Djerid (Southern Tunisia) with a mean salinity of 142 PSU [17]. Chott El-Djerid (5.…”
Section: Methods Of Cultivation and Antioxidant Assays 21 Isolation mentioning
confidence: 99%